(untitled) (ҚазҰУ Хабаршысы. Математика, механика, информатика сериясы, 2020)
Smart greenhouse is a revolution in agriculture, which creates a self-regulating micro climate suitable for plant growth through the use of sensors, actuators and control and management systems that optimize growth conditions and automate the growin g pro cess. The global smart greenh ou se market was valued at approximately 680.3 m illion in 2016 and is exp ected to reach approximately 1.31 billion by 2022, an inc re ase of 14.12% on average b etween 2017 and 2022. However, high installation prices and high upfront investment costs can constrain greenhous e adoption in many underdevelop ed and developing countries. The re fore, the u rgent task is the development and implementation of smart greenhouses that are suitable for the w ider p opulation, which provide the p opulation with vegetables and fruits seasonally or year-round. Improving the quality of service of greenhouses, controlling and monitoring micro clim ate pro cesses is p ossible through the use of programmable logic controllers, mo dern smart, wireless and web te chnologies WSN and IoT. The article is devoted to the design of the Home Smart Greenhouse system, the control device of which is implemented on the basis of NLC. The system allows you to p erform a) control (monitoring) of micro climate pro cesses in Online mo de; b) fuzzy control in manual and automatic mo de; c) adjust the parameters of the three micro climate pro cesses: co oling, watering and lighting. The describ ed NLC mo del adequately reflects the micro climate control pro cess in the greenhouse. As a result of using the system, the pro ductivity of the farmer user is increased, thereby helping the farmer user control the plant growth pro ces s and take the necessary measures to care for them. The develop ed system meets the criterion of price-quality, that is, it is simultaneously acc essible to the p opulation, and at the same time has an acceptable quality of service, using wireless network and web te chnologies (WSN, IoT) and fuzzy control. The cost of the system is 86.75 (the price is not higher than the minimum wage of Kazakhstan), the economic effect of using the system is 25, the payback p erio d of the greenhouse is 4 seasons.